Effects of Red Mold Rice Produced from Monascus purpureus CMU002U on Growth Performances and Antioxidant Activity of Japanese Quail - Kongbuntad, W.; Saenphet , S. (International Journal of Poultry Science, 2015)
This study researched the effects of red rice produced from San-Pah-Tong sticky rice (Oryzae sativa L.cv. Niew San-pah-tawng) and Monascus purpureus (Specie CMU002U). The study was divided into two parts. The first part consisted of a phytochemistry test and tests to determine ascorbic acid and phenolics. Terpenoids, triterpenoids, flavonoids, phenols, phlobatannins and coumarins were found. Phenolic and ascorbic acid levels were 3.00 μg ascorbic acid equivalent/g extract and 1.89 mg Gallic acid equivalent/g extract, respectively. The second part was an experiment using 75 Japanese quails in egg stage randomly divided into four groups as follows: the control group and groups in which each quail was fed with 6, 12 and 24 mg. red rice powder in capsules per day, respectively for 8 weeks. The Manlondialdehyde (MDA) from the serum and liver was then checked. It was found that the serum of the group which received 24 mg a day had reduced levels of MDA in the serum and liver. Compared with the control group, the difference was statistically significant at (p<0.05). After evaluation of body weight, consumption and survival rate of eggs in each group, no difference was found in body weight, but the control group consumed significantly more food than the others (p<0.05). Meanwhile, the group which received 12 mg a day produced significantly more eggs than the control group (p<0.05). Therefore, the antioxidants in red rice can reduce the amount of MDA in the serum and liver of Japanese quails. The fermentation of red rice can affect growth and production and it might be effective to decrease the toxicity of substances in Japanese quail.